Symptomatic COVID-19 in Pregnancy: Hospital Cohort Data between May 2020 and April 2021, Risk Factors and Medicolegal Implications - Marianna Maranto; Simona Zaami; Vincenzo Restivo; Donatella Termini; Antonella Gangemi; Mario Tumminello; Silvia Culmone; Valentina Billone; Gaspare Cucinella; Giuseppe Gullo (Diagnostics, 2023)
Pregnancy does not appear to increase susceptibility to SARS-CoV-2 infection, but some physiological changes, such as the reduction of residual functional volumes, elevation of the diaphragm, and impaired cellular immunity, may increase the risk of severe disease and result in a higher risk of complications. The article’s primary objective is to evaluate the factors associated with symptomatic COVID-19 disease in pregnancy. The secondary objective is to describe maternal and neonatal outcomes and cases of vertical transmission of the infection. All pregnant women hospitalized with SARS-CoV2 infection were included in a prospective study in the UOC of Obstetrics and Gynecology, AOOR Villa Sofia—Cervello, Palermo, between May 2020 and April 2021. The patients who requested the termination of the pregnancy according to Law 194/78 were excluded. We included 165 pregnancies with a total number of 134 deliveries. Overall, 88.5% of the patients were asymptomatic at the time of admission and 11.5% were symptomatic. Of them, 1.8% of the patients required hospital admission in the intensive care unit. Symptoms occurrences were positively associated with the increase in maternal BMI (OR 1.17; p = 0.002), the prematurity (OR 4.71; p = 0.022), and at a lower birth weight (OR 0.99; p = 0.007). One infant tested positive for SARS-CoV2 nasopharyngeal swab; 11.4% of newborns had IgG anti SARS-CoV2 at birth; IgM was positive in 2.4% of newborns. There was no difference statistically significant difference in the vertical transmission of the infection among the group of symptomatic pregnant women and that of asymptomatic pregnant women.